2019
DOI: 10.1186/s12884-019-2584-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the trajectories for women and their babies from births planned at home, in a birth centre or in a hospital in New South Wales, Australia, between 2000 and 2012

Abstract: BackgroundIn New South Wales (NSW) Australia, women at low risk of complications can choose from three birth settings: home, birth centre and hospital. Between 2000 and 2012, around 6.4% of pregnant women planned to give birth in a birth centre (6%) or at home (0.4%) and 93.6% of women planned to birth in a hospital. A proportion of the woman in the home and birth centre groups transferred to hospital. However, their pathways or trajectories are largely unknown.AimThe aim was to map the trajectories and interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The latter is consistent with findings by McNiven et al (2011), who found that 97% of midwives versus 29% of obstetricians agreed that out‐of‐hospital birth centers provide safe care 41 . These beliefs of medical staff are not consistent with evidence that has found out‐of‐hospital birth is safe for women with low‐risk pregnancies 42–44 . However, the disciplinary differences are not surprising given the conflicting recommendations in relation to home birth by medical 45 versus midwifery guidelines 46 .…”
Section: Discussionmentioning
confidence: 88%
“…The latter is consistent with findings by McNiven et al (2011), who found that 97% of midwives versus 29% of obstetricians agreed that out‐of‐hospital birth centers provide safe care 41 . These beliefs of medical staff are not consistent with evidence that has found out‐of‐hospital birth is safe for women with low‐risk pregnancies 42–44 . However, the disciplinary differences are not surprising given the conflicting recommendations in relation to home birth by medical 45 versus midwifery guidelines 46 .…”
Section: Discussionmentioning
confidence: 88%
“…Figure 2 illustrates these potential pathways and the number of women in the sample who followed each pathway are presented below each branch. A description of the conditional probabilities of each pathway has been presented in a previous publication [ 15 ]. Briefly, the normal vaginal birth rate in women planning a homebirth was 96.2% (including women who transferred to hospital), 91.1% for women planning birth in a birth centre (including transfers) and 79.5% in the hospital birth group.…”
Section: Resultsmentioning
confidence: 99%
“…This study used a decision analytic modelling framework to construct a decision tree which illustrated the pathways of women at low risk of complications who gave birth in NSW between 2000 and 2012 [ 15 ]. The pathways were developed by identifying planned place of birth, and then using descriptive statistics, we determined each pathway including planned and actual place of birth, transfer to hospital labour ward, mode of birth and possible admission to neonatal care unit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are more birth centers than home birth programs in Australia, but only marginally. In 2016, there were at least 10 birth centers in NSW—five colocated on hospital premises or adjacent to hospital labor wards, and five midwifery‐led, free‐standing birth centers 43 . Pregnancy Birth and Beyond Pty Ltd lists 24 birth centers across Australia on their website, 44 catering to the 2.4% of Australian births 22 .…”
Section: Discussionmentioning
confidence: 99%